Análise da expressão da indoleamina 2,3-dioxigenase e de suas vias no processo de invasão de células de câncer de bexiga - Santos, Hellen Joyce de Sousa Pereira dos (2019)
Cancer accounts for one in six deaths world wide. Among the most common in men is bladder cancer (CB). The most common form of CB is non invasive muscle, with half of these cases relapsing after conventional treatment and a significant portion evolving to invasive muscle form, leading to metastasis and death. Indolamine 2,3-dioxigenase 1 (IDO1) is an enzyme currently recognized as an immunomodulator since its role in protecting embryonic tissue against the maternal immune system has been demonstrated. IDO has been studied in several types of cancer and has been identified as a key in tumor escape to host immune surveillance. However, there is evidence that IDO participates in non-immune phenomena, one of them being tumor invasion. In a previous study, we demonstrated that the expression of IDO1 is related to the epithelium-mesenchymal transition phenomenon, an important cellular phenomenon in tumor invasion. However, it is not yet know the expression of IDO is constitutive in CB or if it is influenced by the microenvironment, being strategic in the tumor evolution. The aim of the study was to verify if the expression of IDO1 is constitutive in established CB strains and if it changes during the tumor invasion process. Additionally, check if their activation pathways are changed in the same process. The study consisted of an in vitro phase and an in vivo phase. In the in vitro phase, the main cell used was T24, a human strain of muscle-invasive bladder carcinoma. IDO expression was analyzed in this cell by real-time PCR and compared with RT4 cells, a non-invasive human muscle carcinoma strain. To analyze the invasion process, T24 cells were seeded in Matrigel/transwell system for 24 hours and classified as invasive cells (IC) and non invasive cells (NIC). The expression of IDO and marker genes of the activation of their GCN2 and AHR pathways between these two subpopulations, both after invasion and after subculture, was analyzed. To assess the influence of IDO on invasion, T24 cells were induced with INF-gamma, a potent IDO inducer, and incubated with interfering RNA for IDO or chemical inhibitor to inhibit their expression and activity, respectively. In the in vivo phase, the orthotopic and ectopic murine CB models were used to evaluate the expression of IDO by immunohistochemistry. The results showed that T24 cells express more IDO when compared to RT4. In the comparison results between NIC and IC, there was a decrease in IDO1 expression soon after migration, but it was lost when the cells were subcultured for 18 days. Regarding invasion capacity, when cells were treated with INFγ, there was a significant in crease in IDO1 expression in T24 cells, significantly reducing the invasion rate when compared to untreated cells. The same result regarding invasion rate was demonstrated when using siIDO, translational inhibition of IDO significantly inhibited cell invasion in the Matrigel/Transwell system. In the in vivo phase, IDO1 expression was predominant low in tumor cells in areas of invasion of the muscles, and the cells farther from the forehead (periphery) expressed more IDO1. Our results corroborate other studies, raising the hypothesis that CB cells express different levels of IDO1 and that this on the T24 cell phenotype by intensifying tissue invasive.